A new species of the genus Zalophotrema (Digenea: Campulidae), Zalophotrema atlanticum n. sp., from the liver of the striped dolphin Stenella coeruleoalba (Meyen, 1833) (Cetacea: Delphinidae) in Atlantic waters - Abril, E.; Balbuena, J. A.; Raga, J. A. (Systematic Parasitology, 1991)
Zalophotrema atlanticum n. sp. from the liver of a striped dolphin, Stenella coeruleoalba (Meyen, 1833), stranded in the Canary Islands is described. This new species differs from the other Zalophotrema species in body dimensions and relative size and position of the suckers and cirrus-sac. This is the first record of a species of the genus Zalophotrema in the striped dolphin, and the Atlantic Ocean constitutes a new locality record for this genus.